Education Based on Local Wisdom: An Alternative Model for the Integration of Cultural Values in The School Curriculum In Indonesia - Rasidi, Rasidi; Istiningsih, Galih; Masithoh, Robiul Fitri; Rosyidi, M Imron (EDUPEDIA Publisher, 2025)
Amidst rapid globalization, Indonesia's education system faces the challenge of preserving cultural identity. This research develops a model for integrating cultural values into the school curriculum to strengthen identity. The method involves analyzing national policies, developing culture-based curricula, providing teacher training, and fostering local community collaboration. Data were collected via document reviews, observations, and interviews with stakeholders. Findings reveal that integrating cultural values positively impacts students' understanding of diversity, enhances learning engagement, and strengthens character and cultural identity. The study highlights strategies like policy dissemination, culture-based curriculum development, extracurricular activities, community collaboration, multicultural approaches, project-based learning, and teacher mentoring. It also emphasizes cultural preservation through documentation. The proposed SIIEMEI model outlines practical steps from school-community collaboration to exploring local wisdom. Integration measurement methods include classroom observation, student work and attitude assessment, and comprehensive qualitative and quantitative data analysis. This research provides an effective framework for cultivating a generation rooted in culture and prepared for the global world.